ANALISIS NILAI TAMBAH DAN STRATEGI PENGEMBANGAN USAHA PENGOLAHAN ULAP DOYO (Curculigo latifolia) DI KELURAHAN LOA IPUH KABUPATEN KUTAI KARTANEGARA - Alaydrus, Ali Zainal Abidin (SINTA Journal (Science, Technology, and Agricultural), 2022)
The method used in this study is descriptive, while the implementation technique uses survey techniques. The selection of research locations was carried out and the samples selection or key informants was done purposively. The target samples were 15 craftsmen in the Loa Ipuh, Kutai Kartanegara regency, for marketers data sources, researchers used snowball sampling. The key informants at the level of government agencies are people who are competent and have a relationship with the existence of Ulap doyo business. Method to find out the value added using Hayami method. While to find out the development strategy is carried out using a SWOT analysis. Based on the value added analysis of ulap doyo  processing industry in Loa Ipuh district, the business was able to produce added value of lDR. 2,728,929 per kilogram input of ulap doyo thread. The value added ratio owned is 76,952 percent. Based on the external internal analysis of SWOT, the ulap doyo processing business in Loa Ipuh district is in Quadrant I, a strategy that can be done to develop the business is an expantion strategy. This means that this strategy uses internal forces to reach opportunities. Key Words: Ulap Doyo, Added Value, Development Strategy